KESEJAHTERAAN SUBJEKTIF SEORANG ISTRI YANG BERPOLIGAMI DI PALEMBANG (PENDEKATAN FENOMENOLOGIS) - Fajarwati, Urfaa (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2015)
This study aims to determine subjective well-being a wife polygamy includes happiness , life satisfaction and perceived anxieties and the factors that influence subjective well-being.Subject in this study amounted one person. This subject is a wife polygamy by her husband around 11 years, age 50 years old and is ail Diabetes Mellitus.The approach taken in this qualitative study is a phenomenological approach. Data collection tool using the method of observation, interviews and documentation. Analisys data used Epoche, Phenomenological reduction, Imaginative variation, Synthesis of meaning and essences. The conclusions drawn researchers, the subject in this study haven?t subjective weel-being. Thus are things can describe abaout subjective wife polygamy are happiness, life statification and anxiety were knew subject unfeeling happiness of life because her husband had polygamous, unfeeling life statification because  not satisfied completely had her husband and anxiety because subject more negative thinking of the problems that occur as a result of her husband's polygamous